Capillary electrophoretic analysis of ionic content in exhaled breath condensate and pH monitoring as a non-invasive method in gastroesophageal reflux disease diagnostics - Lačná, Júlia; Ďurč, Pavol; Greguš, Michal; Skřičková, Jana; Doubková, Martina; Pokojová, Eva; Kindlová, Dagmar; Dolina, Jiří; Konečný, Štefan; Foret, František; Kubáň, Petr (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2019)
In this study, the ionic profile and pH of exhaled breath condensate (EBC) in a group of patients with acid and weakly acid reflux and no-reflux controls were compared. A portable sampler was used for non-invasive EBC collection from five exhalations. The ionic profile (anions, cations, organic acids) and pH of the collected EBC samples were measured by capillary electrophoresis with contactless conductivity detection and a pH microelectrode, respectively. Several ions were elevated in the patient groups. Sodium cation was elevated in weakly acid reflux (significance level p < 0.01) and acid reflux (p < 0.05) compared to no-reflux controls. Butyrate and propionate were elevated in both acid reflux and weakly acid reflux compared to no-reflux controls (butyrate: p < 0.01, propionate: p < 0.05). The median values of pH (after de-aeration with N2) were also significantly higher (p < 0.01) in groups with acid reflux and weakly acid reflux than in the control group with no reflux. The ionic analysis and simultaneous pH measurement offer a simple, cheap, fast, and non-invasive approach in gastroesophageal reflux disease diagnostics.
Keywords: Female; lidé středního věku; dechové testy; gastroezofageální reflux; Gastroesophageal Reflux; Electrophoresis, Capillary; elektroforéza kapilární; mužské pohlaví; koncentrace vodíkových iontů; ionty; Propionates; Humans; dospělí; Hydrogen-Ion Concentration; Sodium; lidé; Middle Aged; sodík; senioři; Butyrates; butyráty; ženské pohlaví; Ions; Aged; Breath Tests; propionáty; Adult; Male